Et Peder Låle-ordsprog skrevet med runer - Lerche Nielsen, Michael (Danske Studier, 2024)
The paper discusses a runic annotation in a Swedish law-code manuscript from the fourteenth century, Copenhagen AM 53, 4o. By using a new technique, multispectral photo analysis, it has been possible to identify the inscription as a Latin proverb from the medieval collection attributed to Peder Låle: Crura refarcire bursis et dentibus ire / Nostras insolitum statuit fieri sibi ritum. The runic annotation shows young features which date the inscription to the 16th century. The new-find consolidates a hypothesis of an error, resarcire instead of refarcire, in the printed versions of this proverb from the sixteenth century. Furthermore, the occurrence of a proverb in a law codex and similar additions in other manuscripts raises questions about why runes should have been used in the late medieval period and the Renaissance. It is most probable that runes at that time reflect a growing nationalistic fervour.